Penghambatan Proliferasi Limfosit Mencit Balb/c oleh Ekstrak Testis Sapi Bali: Peran TGF-β - S N Depamede; A Rosyidi (Faculty of Animal Science, Bogor Agricultural University, 2009)
Testis extract (ET) of several animals such as rats, mice, boars, and bulls, has been reported able to suppress lymphocyte proliferation. In order to elucidate if ET of bali cattle has the suppressive activity, the present study was conducted. ET was isolated aseptically from the testis of bali cattle slaughtered at a slaughter house in Mataram, Lombok. After decapsulating, the testis were minced, homogenized (1 g tissue per 3 ml phosphate buffered saline, PBS, pH 7.2). The ET (40, 20, and 10µg/ml) was added on to lymphocytes isolated from Balb/c spleen, then cultured for 72 hours in RPMI media containing 10% foetal bovine serum in 96 well plates with the concentration of 250,000 cells per well, with- or without concanavalin A (10 µg/ml), or IL-2 (0.2 ng/ml). After 72 h of culture, cell proliferation was examined by colorimetric assay. The results showed that bali cattle ET were able to suppress the proliferation of lymphocytes in vitro through the process of apoptosis. Western blot analysis revealed that bali cattle ET contain TGF-β1. The suppression effects of the ET were eliminated by anti-TGF-β1 antibody. It can be concluded that ET of bali cattle expressed TGF-β which inhibited lymphocyte proliferation through an apoptotic cell mechanism. The actual roles of TGF-β in the bali cattle testis need to be elucidated further. Key words: bali cattle testis, lymphocyte, proliferation, TGF-β1, apoptosis